2011
DOI: 10.1021/ac201658s
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Design and Analysis of Multivolume Digital Assays with Wide Dynamic Range Validated Experimentally with Microfluidic Digital PCR

Abstract: This paper presents a protocol using theoretical methods and free software to design and analyze multivolume digital PCR (MV digital PCR) devices; the theory and software are also applicable to design and analysis of dilution series in digital PCR. MV digital PCR minimizes the total number of wells required for “digital” (single molecule) measurements while maintaining high dynamic range and high resolution. In some examples, multivolume designs with fewer than 200 total wells are predicted to provide dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
183
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(189 citation statements)
references
References 74 publications
6
183
0
Order By: Relevance
“…Few authors, however, have yet investigated the application of this technology to infectious disease diagnostics. Experimental systems have demonstrated proof of principle for quantification of adenoviral genome copies, GB virus in transfected cell culture lines, serial dilutions of hepatitis C virus and HIV RNA, and purified, serially diluted HIV RNA from two clinical samples (19,30,31). The latter studies demonstrated a 4-log 10 -unit linear range and variable agreement with real-time PCR methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few authors, however, have yet investigated the application of this technology to infectious disease diagnostics. Experimental systems have demonstrated proof of principle for quantification of adenoviral genome copies, GB virus in transfected cell culture lines, serial dilutions of hepatitis C virus and HIV RNA, and purified, serially diluted HIV RNA from two clinical samples (19,30,31). The latter studies demonstrated a 4-log 10 -unit linear range and variable agreement with real-time PCR methods.…”
Section: Discussionmentioning
confidence: 99%
“…Droplet digital PCR (ddPCR) is such a direct method (17)(18)(19)(20)(21)(22). It relies on limiting partition of the PCR volume, such that a positive result in any of a large number of microreactions (in this case, 20,000) indicates the presence of a single target molecule in a given reaction.…”
mentioning
confidence: 99%
“…Moreover, it was found that MV-dPCR offers a wider dynamic range and better sensitivity than single-volume dPCR assays. 44,45 Fig . 5A shows a representative fluorescence image for the end-point dPCR detection of a l-DNA sample using a mixture of four differently sized droplets.…”
Section: 42mentioning
confidence: 99%
“…Gregory L. Shipley, 11 Jo Vandesompele, 6 Carl T. Wittwer, 12 and Stephen A. Bustin 13 There is growing interest in digital PCR (dPCR) because technological progress makes it a practical and increasingly affordable technology. dPCR allows the precise quantification of nucleic acids, facilitating the measurement of small percentage differences and quantification of rare variants.…”
mentioning
confidence: 99%